The Urgency in Legal Protection Of The Internment in Non-International Armed Conflict Between The Ethiopian Government and The Tigray People’s Liberation Front - Ningtyas, Ika; Putri, Maheswari Trinanda; Rachmawati, Yasniar; Susanto, Fransiska A.; Ruslijanto, Patricia Audrey (UI Scholars Hub, 2024)
The issue of a legal vacuum in international humanitarian law related to administrative internment in non-international armed conflicts has been a concern addressed in Article 3 of the Geneva Convention and Articles 5-6 of Additional Protocol II. Due to this deficiency, many countries establish their domestic laws. One such example is the non-international armed conflict between the Ethiopian government and a non-state armed group, the Tigray People’s Liberation Front. The issue in this case began with the government's emergency statement for a six-month period, granting broad authority to arrest individuals based on “impossible judgment” and cooperation with a “terrorist group” without a judicial statement. This research aims to analyze the internment taking place in Ethiopia in accordance with the Proclamation of State of Emergency of Ethiopia Number 5 of 2021. The research employs normative-juridical methods, including statutory, case, and conceptual approaches. The results show that there are legal loopholes regarding internment in the non-international armed conflict, leading to arbitrary internment done by all parties involved in the armed conflict in Ethiopia. Therefore, a new concept is required to regulate the procedure of internment in international armed conflicts, aiming to realize legal protection for the prisoners. This procedure can refer to the existing regulations concerning internment in the case of international armed conflict within the international humanitarian law regime of Geneva Convention IV and the Internment Regulation in the international human rights law regime.